Examination of Volatile Organic Compounds From Building Products in Terms of Building Biology - Darcin, Polat; Balanli, Ayse (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
Volatile organic compounds (VOCs) are within important pollutant groups which cause indoor air pollution and many serious health problems. VOCs include hundreds of different pollutants with similar properties and can easily volatilize at low temperatures. In order to avoid problems, negativities caused by VOCs in the building and its environments and the effects on human health must be determined. In this study, an examination and relations model, produced for this purpose in the field of building biology, is used. The process of this model includes the determination of a negative feature in building: building products with VOCs, a negative condition: VOCs in indoor air, a hazardous effect: being exposed to VOCs and many health problems. The research has shown that many different building products may contain VOCs. The indoor environment conditions are effective on emission properties. It has been understood that indoor air concentrations of these pollutants are mostly much higher than outdoor concentrations in many studies. For the exposure of users, not only the type of pollutants but also the properties of exposure are effective. In order to avoid negative effects or to reduce the concentrations, it is advised not to prefer VOCs containing building products, to control their usage conditions and to supply accurate ventilation in buildings. Recommendations are provided for future researches.
Keywords: Volatile organic compounds; building biology; indoor air pollution